The Tourism Management Information Searching During Pandemic COVID-19 - Yosephine Angelina Yulia; Tri Widianto; Terrensia Sekar Pamastutiningtyas; Lukman Ahmad Imron P (Universitas Warmadewa, 2022)
Tourism is one of the sectors hardest hit by the COVID-19 pandemic. Based on BPS data (2021), there was a significant decrease in the number of tourists. This study aims to find out how consumers face the fear of the Covid-19 pandemic when they are going to travel through online applications. The research indicators are measures of health, personal, financial stressors, use of travel research and applications and intentions, social media, travel avoidance. The population of this study is potential tourists during the COVID-19 pandemic. The research sample was 105 respondents with a minimum sample size of 5 times the estimated parameters. This research uses the convenience sampling method. The measurement scale used is a Likert scale of 1-5. The data analysis technique used multiple linear regressions. The results of this study revealed that health stressors have a significant effect on the use of research and travel applications. Personal stressors variable and financial stress have no effect on consumers in the use of research and travel applications. The effect of health and personal stress on social media searches is not proven. The use of research and travel applications had no effect on the intention for future book research. While the searches for tourist information on social media affect the intention to book the next search the use of travel research and applications has a significant effect on travel avoidance. This study provides insight into the role of stressors and their influence on tourist information seeking during the pandemic.